2018
DOI: 10.1002/jid.3351
|View full text |Cite
|
Sign up to set email alerts
|

When Do Developing Countries Negotiate Away Their Corporate Tax Base?

Abstract: Developing countries have concluded thousands of bilateral tax treaties, which restrict their 'taxing rights' over international investment. Qualitative case studies of these negotiation outcomes emphasize power politics, knowledge asymmetries and negotiating capability in the eventual distribution of taxing rights between signatories, yet such insights are absent from crosscountry quantitative work. This paper bridges the gap by replicating two quantitative studies, introducing new data on countries' ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…The OECD model reflects the interests of capital exporting countries, because it imposes a solution to the double taxation problem that imposes a larger share of the costs onto the capital importing country (Brooks & Krever, 2015;Dagan, 2000;Genschel & Rixen, 2015;Irish, 1974;Paolini, Pistone, Pulina, & Zagler, 2016;Thuronyi, 2010). Capital-importing developing countries nonetheless seek tax treaties with OECD states as the price of attracting inward investment and because they can ameliorate some of the bias through bilateral negotiations (Barthel & Neumayer, 2012;Chisik & Davies, 2004;Hearson, 2018;Rixen & Schwarz, 2009). 3 Because they primarily constrain states' ability to tax inward investment, tax treaties are potential instruments of tax competition, offering inward investors a more credible commitment to a lower effective tax rate in the future than domestic law alone would provide (Baistrocchi, 2008;Barthel & Neumayer, 2012).…”
Section: The State-centred View Of the International Tax Regimementioning
confidence: 99%
“…The OECD model reflects the interests of capital exporting countries, because it imposes a solution to the double taxation problem that imposes a larger share of the costs onto the capital importing country (Brooks & Krever, 2015;Dagan, 2000;Genschel & Rixen, 2015;Irish, 1974;Paolini, Pistone, Pulina, & Zagler, 2016;Thuronyi, 2010). Capital-importing developing countries nonetheless seek tax treaties with OECD states as the price of attracting inward investment and because they can ameliorate some of the bias through bilateral negotiations (Barthel & Neumayer, 2012;Chisik & Davies, 2004;Hearson, 2018;Rixen & Schwarz, 2009). 3 Because they primarily constrain states' ability to tax inward investment, tax treaties are potential instruments of tax competition, offering inward investors a more credible commitment to a lower effective tax rate in the future than domestic law alone would provide (Baistrocchi, 2008;Barthel & Neumayer, 2012).…”
Section: The State-centred View Of the International Tax Regimementioning
confidence: 99%
“…Research has shown that the former unequal power relationship between negotiating states was passed on in the tax treaty negotiation process. For instance, Martin Hearson has uncovered that tax experts from the UK dictated the terms of the tax treaties by insisting on source-restricting tax treaty provisions based upon the OECD MTC (Hearson 2016(Hearson , 2017(Hearson , 2018.…”
Section: The Historical Backgroundmentioning
confidence: 99%
“…But why would developing states accept tax treaty provisions that harm their tax bases? The legal doctrine dealing with this issue indicates that there is no easy answer (Ring 2009(Ring , 2010Hearson 2018), but some more general reasons are often touched upon. Without concluding any tax treaties at all they would not be able to attract foreign direct investment (FDI), and additionally be locked out of any influencing outside of their own domestic 3 Prosper in this context should be put in relationship with the fact that most African states currently suffer from extreme poverty.…”
Section: The Historical Backgroundmentioning
confidence: 99%
“…The study by Hearson () examines the determinants of having a tax treaty. In principle, tax treaties are meant to make sure foreign firms are not double taxed on the profits they earn abroad, thus making countries with treaties more attractive as investment destinations.…”
Section: This Collectionmentioning
confidence: 99%